PENDAMPINGAN LITERASI PERAN PEREMPUAN PADA PENCATATAN AKUNTANSI RUMAH TANGGA - Siti Hartinah; Rindu Ferdina Lestari; Hairul Triwarti; Hamli Syaifullah; Nadia Rahmadhanti; Ajeng Setio Mardiani (Media Resonansi Pengabdian Masyarakat, 2025)
This community service program aims to enhance household financial literacy, strengthen the role of women in basic financial record-keeping, and introduce the utilization of financial technology (FINTECH) in daily financial management. The target group of this program was a community of housewives located at Jalan Mushollah Nurul Amal, Tangerang, with Ms. Nani Rohaini serving as the main partner. The implementation method was structured into three stages: preparation, execution, and evaluation. The preparation stage involved conducting a preliminary survey, analyzing partner needs, developing educational materials, and assigning tasks among the academic team members. The execution stage was carried out through an interactive lecture method, discussions, practical exercises in daily transaction recording, and the introduction of e-banking and digital wallet services. Evaluation was conducted through direct observation, questionnaires, interviews, and group discussions to assess participants' understanding and the effectiveness of the program. The results demonstrate a significant improvement in participants’ awareness of the importance of systematic financial recording, their ability to create basic household financial records, and their readiness to utilize digital financial services. This program highlights the critical role of empowering women in strengthening family economic resilience through enhanced financial literacy. Future plans include follow-up visits and the development of digital-based learning modules to ensure sustainable impacts. Overall, this community service initiative provides tangible contributions to strengthening household financial management capacity through literacy and technology integration.Keywords: Financial Literacy, Household Accounting Records, Women Empowerment, Financial Technology (FINTECH), Community Service.